THE INFLUENCE OF FLASHCARD MEDIA USING THE CANVA APPLICATION ON THE DIFFICULTY OF LEARNING TO READ THE BEGINNING OF THE THEME OF MY ACTIVITIES IN GRADE I SD NEGERI 064972 MEDAN DENAI - Widya Gauri Sasqia Putri; Dalimawaty Kadir (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Flashcard learning media is a simple media that can be used by teachers in carrying out the reading learning process for students. Flashcards are a type of learning media in the form of graphics in the form of small cards with pictures, usually made using photos, symbols or pictures that are attached to the front side and the back side contains information in the form of words or sentences from the flashcard image. The advantages of this flash card game media can motivate students in learning and foster students' enthusiasm for learning in improving students' vocabulary skills in learning. The objective of this research was to analyze the influence of flashcard media using the Canva application on difficulties in learning to read. The beginning of my activity theme in grade 1 of SD Negeri 064972 Medan Denai. The research uses quantitative research. This research uses research instruments in the form of a pretest and posttest to test the effect of using flashcard media using the Canva application on difficulties in learning to read at the beginning of my activity theme in grade 1 of SD Negeri 064972 Medan Denai. Based on research on the influence of flashcard media on the initial reading difficulties of grade I students at SD Negeri 064972 Medan Denai, it can be concluded that there is an influence of flashcard media on the initial reading difficulties of grade I students at SD Negeri 064972 Medan Denai. This is known based on the t hypothesis test, the final data shows that tobserved is greater than ttable or 3,279 > 1,724 with a significance level of α= 0.05, so it can be concluded that flashcard media has a positive and significant influence on the initial reading difficulties of grade I students at SD Negeri 064972 Medan Denai.